Perilaku Verbal Abuse Orang Tua Dan Agresifitas Remaja - Aris Fitriyani; Esti Dwi Widayanti (Prodi Keperawatan Purwokerto, 2020)
Children aged three years who often suffer abuse from their parents will be aggressive at school age. Aggressive behavior will increase in line with the more frequent abuse experienced by children. To analyze the effect of verbal abuse behaviors of parents and aggressive adolescents.This study is a quantitative and qualitative research. Design research pre-post test and interview one-group design. Intervention by providing ways to stop the violence and the emotional impact of verbal abuse. 3 junior high student population in Private Purwokerto number of 607 students. The sample was taken by purposive sampling based on inclusion and exclusion criteria. The sample size is based on the formula Slovin many as 241. Location Yos Sudarso Sokaraja JSS research, Sokaraja Muhammadiyah junior high school, and junior high Kalibagor PGRI. The analysis used Pairs T-test with an error rate (alpha) used is 5% or 0.05.The majority of respondents 13 years of age, male gender, media and internet frequently watched TV, the spectacle of violence rarely seen, maternal age 20-61 years, 27-82 years of age of the father, mother and father's education respondents SD, is the mother's occupation household and respondent father's work is labor. No influence of verbal abuse of parents of adolescent aggressive behavior and there was no significant difference about the verbal abuse and agresifias adolescents with £ p≥ results.